Action Algorithm for the Diagnosis of Prostate Hyperplasia in Dogs - Tatyana S. Mychko1 , Ivan I. Silkin2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In veterinary practice, at present, specialists often have to deal with pathology of the prostate gland in dogs. The reason for this is that the pathological process in the tissues of the prostate gland can occur asymptomatic and for a long period of time, subsequently leading to organ hypertrophy. An increase in the volume of the prostate gland most often has a benign character, which is generally accepted to be diagnosed as prostatic hyperplasia. The disease is often detected at a late stage, which complicates the treatment and worsens the prognosis. Hyperplasia, as a medical condition, is an indicative term used to describe the abnormal increase in the number of cells in any organ, in this case the prostate gland. This article describes the main symptoms, diagnostic methods and differential diagnosis proceeding from practical veterinary experience.